Penerapan Model Pembelajaran Direct Instruction (Di) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Kearsipan di SMK Negeri 1 Limboto Kabupaten Gorontalo - Anugra A. Utumbala; Irina Popoi; Irawati Abdul (Jambura Economic Education Journal, 2019)
This research aims at improving students learning achievement in archives through the implementation of direct instruction learning model at grade X ADP 1, SMK NEGERI 1 Limboto. It applies Classroom Action Research, Samples are 24 students consisten of 4 males and 20 famales at grade XADP 1 in archives. This is a Clasroom action research consisting of 2cycles which is cycle I and II. Analysis in cycle I shows that out of 24 students 9 or 37,5% obtains score ? 75 while the rest 15 or 62,5% obtains score of 75 and 2 students (8,33%) obtain score of less than 75.Therefore, it can be concluded that the application of direct instruction learning model can improve students learning achievement in archieve subject atSMK Negeri Limboto District of Gorontalo.